A State-space Approach for Efficient Channel Tracking in OFDM Transmissions - Pedrosa, P.; Castanheira, D.; Silva, A.; Dinis, R.; Gameiro, A. (IEEE Vehicular Technology Conference, 2020)
In this paper we consider a multipath channel subject to variations in time due to the presence of a Doppler term which imposes a phase rotation on the original channel impulse response. Accordingly, a decision-directed state-space approach based on the extended Kalman filter (EKF) is proposed to track the channel variation. This approach is particularly efficient since we are able to reduce the number of pilot symbols used for channel tracking by using a decision-directed approach. In fact, only two training symbols are required to initialize the EKF. Our approach is validated considering orthogonal frequency-division multiplexing (OFDM) schemes.